The Effect of Profitability, Independent Commissioners, and Firm Size on Firm Value (in Processed Food Sub-Sector Companies Listed on the Indonesia Stock Exchange for the 2020–2024 Period) - Ira Sukmawati; Rawi Rawi (Universitas KH. Abdul Chalim Mojokerto, 2026)
This research seeks to examine the influence of profitability, the presence of independent commissioners, and firm scale on corporate valuation within processed food sub-sector companies listed on the Indonesia Stock Exchange (IDX) over the 2020–2024 timeframe. The study adopts a quantitative design, utilizing secondary data derived from corporate annual reports. A total of 17 firms were selected through purposive sampling, yielding 85 observational data points. The analytical technique employed is panel data regression processed with SPSS software. The findings indicate that profitability exerts a positive and statistically significant impact on firm value, whereas independent commissioners do not demonstrate a meaningful influence. Conversely, firm size exhibits a negative yet significant relationship with firm value. Collectively, profitability, independent commissioners, and firm size simultaneously present a significant effect on corporate valuation. This study is anticipated to contribute empirically to the advancement of signaling theory and agency theory, while also offering insights for investors, corporate management, and policymakers in enhancing firm value within the processed food sub-sector.